STRUCTURAL GENETIC INTERPRETATION OF THE NOVEL “NEW CATATAN HATI SEORANG ISTRI” BY ASMA NADIA - Syamhari; Iskandar (Elite : English and Literature Journal, 2025)
This study explores the genetic structure in Asma Nadia’s novel “New Catatan Hati Seorang Istri”, focusing on the relationship between the elements that construct the text and the social context that underlies the author’s creative process and the readers’ reception. This study focuses on the representation of human facts in the story and how the author’s worldview is articulated through themes, characters, plot, and other narrative constructions. Thus, the analysis is conducted to reveal the interconnection between the intrinsic structure of the novel and the social reality that is presented and responded to by readers. The research method is qualitative-descriptive, with a text analysis approach assisted by structural and sociocultural theoretical frameworks. The results show that the main theme of the novel focuses on women’s struggles in facing domestic dynamics and conflicts. Female characters are portrayed as patient, strong, and religious individuals. The mixed plot, domestic setting, and emotional style of language reinforce the moral message of the story. Analysis of the author’s worldview reveals a deep empathy for women’s inner struggles, while readers perceive the social reality of the emotional burden, injustice, and determination of a wife in maintaining family unity